The Relationship Between Quality of Life of Adolescents with Thalassemia and Parents' Quality of Life: A Cross Sectional Study - Tarigan, Sri Yenni Br; Mardhiyah, Ai; Witdiawati, Witdiawati (Indonesian Journal of Global Health Research, 2024)
Thalassemia is a lifelong genetic disorder that requires regular and routine treatment. Adolescents with thalassemia major experience changes in physical, emotional, school, and family. Parents of thalassemia adolescents are the ones who care for and are always involved in the process of caring for their children, this condition can affect the quality of life. This study aims to identify the relationship between the quality of life of adolescents with thalassemia major and the quality of life of parents at RSUD Dr Slamet Garut. This study is a quantitative study with a cross-sectional approach. The sampling technique was consecutive sampling. Respondents of this study were 64 adolescents with thalassemia major and parents. Data collection was carried out at the time before the patient had a blood transfusion using the TranQol questionnaire and WHOQOL-BREF. TranQol to measure the quality of life of adolescents that has been tested for validity and reliability with a value of r=0,112-0,743 and α=0,806. WHOQOL-BREF to measure the quality of life of parents that has been testet for validity and reliability with a value of r=0,5-0,7 and α=0,41-0,77. The data analysis used was univariate analysis and bivariate analysis using the spearman rank correlation test. The results of this study found that the quality of life of adolescents with thalassemia major at RSUD Dr. Slamet Garut as many as 53 respondents (82.8%) was good, as many as 11 respondents (17.2%) was bad. While the quality of life of parents as many as 61 respondents (95.3%) is good, as many as 3 respondents (4.7%) was bad. Based on the results of the spearman rank test, the results obtained p=0.001 (p<0.05) which means that there is a significant relationship between the quality of life of adolescents with thalassemia major and the quality of life of parents. So it can be concluded that the better the quality of life of adolescents with thalassemia major, the better the quality of life of parents.